The cultural area of the suicidal behaviour - Cornutiu, Gavril; Cornutiu, Oana (Advances in Social Sciences Research Journal, 2014)
There is a cultural fluctuation of suicide. This is known since Durkheim. For this study the authors tried to outline a cultural parameter which influences suicide. Research on a group of 602,206 inhabitants in a romanian county (Bihor) of two nationalities: 70.92% Romanians and 29.05% Hungarians has been carried out. The suicide rates between 01.01.1994 and 31.12.2003 have been analyzed. The data used came from official records – the County Forensic Pathology Laboratory. Suicide rates on distinctive ethnic areas measured in cases per 100,000 population were as follows: rural areas – 34.8 cases in 100,000 population in Hungarians and 3.96 cases in 100,000 population in Romanians; urban areas – 34.37 per 100,000 in Hungarians and 6.55 per 100,000 in Romanians; areas with mixed population (Romanians and Hungarians) 1/1 – rate of suicide 1/1 (16.58). In conclusion, there are Areas of Cultural Vulnerability to Suicide that require the setting up of Principles of Cultural Prophylaxis of Suicide.